2012
DOI: 10.1007/978-3-642-33666-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Automated and Transparent Model Fragmentation for Persisting Large Models

Abstract: Abstract. Existing model persistence frameworks either store models as a whole or object by object. Since most modeling tasks work with larger aggregates of a model, existing persistence frameworks either load too many objects or access many objects individually. We propose to persist a model broken into larger fragments. First, we assess the size of large models and describe typical usage patterns to show that most applications work with aggregates of model objects. Secondly, we provide an analytical framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…However, different experiences have shown that CDO does not scale well to very large models [21,22,24]. Barmpis and Kolovos [4] suggest that NoSQL databases would provide better scalability and performance than relational databases due to the interconnected nature of models.…”
Section: Related Workmentioning
confidence: 99%
“…However, different experiences have shown that CDO does not scale well to very large models [21,22,24]. Barmpis and Kolovos [4] suggest that NoSQL databases would provide better scalability and performance than relational databases due to the interconnected nature of models.…”
Section: Related Workmentioning
confidence: 99%
“…The popular EMF provides the means to partition models with proxies, but lacks support for fragmentation strategies (FSs). To improve this, [11] proposes a non-formal persistence framework for EMF to fragment models along annotated metamodel compositions. Our theory is formal and provides a powerful notion of fragmentation regions that allows metamodel-defined fragmentations along our container primitive of clusters.…”
Section: Related Workmentioning
confidence: 99%
“…First, we built a framework that allows us to collect and represent sensor data in well structured, strictly typed EMF models [15]. Second, we extended EMF's resource API to persist large amounts of sensor data to distributed databases [14,13]. Thirdly, we use model transformation techniques to implement algorithms (work in progress).…”
Section: Emf-based Tools For Experimentationmentioning
confidence: 99%
“…We developed EMF-Fragments [14,13], an EMF-based persistence framework that automatically fragments a model into many resources and maps resources and their URIs to values and keys in a distributed key-value store (as in NoSQL database, e.g. Hadoop's HBase [5]).…”
Section: Emf-fragmentsmentioning
confidence: 99%
See 1 more Smart Citation